Bank marketing at the present Ukrainian banking services market - Shlafman, N.; Hudkov, V. (Економічний вісник Донбасу, 2016)
The high degree of Ukrainian economy’s politicization led to an aggravation of problems in the banking sector, which virtually ceased to perform its function of lending business these days. For an effective functioning of the banking system in the face of growing competition and commercialization of banking activities, the system’s management must include: objective determination of the current and desired state, which is coordinated by the management of financial resources, development of new flexible strategies, innovative management solutions choice, new segments, banking services and service methods development. Western specialists and experts point to the urgent need of improving of strategic and organizational roles of Bank marketing, that is based on effective usage of new information technologies. The basis of the modern Bank marketing is a strategy of maximal customer satisfaction, which, in turn, leads to a significant increase in bank’s profitability.The article considers several still not enough revealed aspects of this scientific problems, especially: analysis of current state of Ukrainian banks’ marketing activities; analysis of marketing service organization in Ukrainian banks; determining of marketing studies, which are preferable for Ukrainian banks; detection of marketing activity problems in Ukrainian banks and determination of transformational market factors.Also, the main trends and development of Bank marketing features are considered, basic types and relationship marketing tools are described. Високий ступінь політизації економіки України призвів до загострення проблем в банківському секторі, який сьогодні практично припинив виконувати свою функцію кредитування бізнесу. Для ефективного функціонування банківської системи в умовах зростаючої конкуренції і комерціалізації банківської діяльності, її управління передбачає: об’єктивне визначення поточного і бажаного стану, скоординоване управління фінансовими ресурсами, розробку гнучких стратегій, вибір інноваційних управлінських рішень, розвиток нових сегментів, банківських послуг і методів обслуговування. Західні фахівці і експерти вказують на нагальну потребу підвищення стратегічної й організаційної ролі банківського маркетингу, що базується на ефективному використанні нових інформаційних технологій. Основою сучасного банківського маркетингу є стратегія максимального задоволення потреб клієнтів, що, у свою чергу, призводить до істотного підвищення рентабельності діяльності банків.У статті розглядаються досі недостатньо розкриті окремі аспекти даної наукової проблематики, зокрема: аналіз сучасного стану маркетингової діяльності банків України; аналіз організації маркетингової служби у банках України; визначення маркетингових досліджень, пріоритетних для українських банків; виявлення проблем маркетингової діяльності українських банків та трансформаційних ринкових факторів.Також розглянуто основні тенденції та особливості розвитку банківського маркетингу у сучасних умовах, визначено основні види та інструменти маркетингу відносин. Высокая степень политизации экономики Украины привела к обострению проблем в банковском секторе, который сегодня практически прекратил выполнять свою функцию кредитования бизнеса. Для эффективного функционирования банковской системы в условиях растущей конкуренции и коммерциализации банковской деятельности, ее управление предусматривает: объективное определение текущего и желаемого состояния, скоординированное управление финансовыми ресурсами, разработку гибких стратегий, выбор инновационных управленческих решений, развитие новых сегментов, банковских услуг и методов обслуживания. Западные специалисты и эксперты указывают на настоятельную необходимость повышения стратегической и организационной роли банковского маркетинга, основанной на эффективном использовании новых информационных технологий. Основой современного банковского маркетинга является стратегия максимального удовлетворения потребностей клиентов, что, в свою очередь, приводит к существенному повышению рентабельности деятельности банков.В статье рассматриваются до сих пор недостаточно раскрытые отдельные аспекты данной научной проблематики, в частности: анализ современного состояния маркетинговой деятельности банков Украины; анализ организации маркетинговой службы в банках Украины; определение маркетинговых исследований, приоритетных для украинских банков; выявление проблем маркетинговой деятельности украинских банков и трансформационных рыночных факторов.Также рассмотрены основные тенденции и особенности развития банковского маркетинга в современных условиях, определены основные виды и инструменты маркетинга отношений.